Influence Of Location On Patient Satisfaction In The Technical Implementation Unit Of Puskesmas Simalingkar Medan - Devi Irawati Tinambunan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat-Universitas Darma Agung. (LPPM_UDA), 2023)
Location is a place of service, related to where the company must be headquartered and carry out its operations or activities. While patient satisfaction is a level of patient feelings that arise as a result of the performance of health services obtained after the patient compares with what is felt. The formulation of the problem that the author wants to know is